2006
DOI: 10.1179/146532806x90556
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional rickets around the world: causes and future directions

Abstract: Rickets exists along a spectrum ranging from isolated vitamin D deficiency to isolated calcium deficiency. Along the spectrum, it is likely that relative deficiencies of calcium and vitamin D interact with genetic and/or environmental factors to stimulate the development of rickets. Vitamin D supplementation alone might not prevent or treat rickets in populations with limited calcium intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
149
4
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(164 citation statements)
references
References 121 publications
(117 reference statements)
0
149
4
11
Order By: Relevance
“…Rickets is the most common bone disease in children worldwide, but data on prevalence are few [56,57]. The disease often afflicts immigrants, including children with dark pigmentation living in low-UVB environments and those living in poverty in cities with little access to recreational sunshine.…”
Section: Diseases Related To Uvb Exposure Insufficient To Maintain Admentioning
confidence: 99%
“…Rickets is the most common bone disease in children worldwide, but data on prevalence are few [56,57]. The disease often afflicts immigrants, including children with dark pigmentation living in low-UVB environments and those living in poverty in cities with little access to recreational sunshine.…”
Section: Diseases Related To Uvb Exposure Insufficient To Maintain Admentioning
confidence: 99%
“…Although the pathophysiology of nutritional rickets and preventive measures are well recognized, the disease is not eradicated in industrialized countries (2). In a study conducted in Copenhagen between 1990 and 1999, only 40 cases of rickets were found, all among immigrant children (3).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency (VDD) is observed in up to 90% of Asian Indians (Goswami et al, 2000;Vupputuri et al, 2006) and is equally prevalent in several other countries (Holick, 2006;Thacher et al, 2006). Though the rise in serum PTH is a well-characterized bio-adaptive response in VDD (Fraser et al, 1967), a majority of volunteers with chronic VDD have normal PTH values (Goswami et al, 2000).…”
Section: Introductionmentioning
confidence: 99%